Broadband beam shaping - Perumal, Leerin Michaela (University of the Witwatersrand, Johannesburg, 2024)
Laser beam shaping is a venerable topic that enjoyed an explosion in activity in the late 1990s with the advent of diffractive optics for arbitrary control of coherent fields. Today, the topic is experiencing a resurgence, fueled in part by the emerging power of tailoring light in all its degrees of freedom, so-called structured light, and in part by the versatility of modern day fabrication and implementation tools. Since its development, structured light has become a priceless tool in various applications such as telecommunication, imaging and microscopy, industrial manufacturing, quantum computing, optical trapping and medical treatments, to name a few. With recent advancements in these various applications, broadband beam shaping (creating structured light with many wavelengths) has become topical as it offers an additional degree of freedom for one to manipulate. In this thesis we look at how to generate broadband light using both digital and physical beam shaping optics. In so doing we provide a method to introduce broadband beam shaping into various applications that may benefit from either the compact size of a physical optic or the dynamic ability of a digital.
A thesis submitted in fulfillment of the requirements for the degree of Master of Science, to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Laser beam shaping; Broadband beam shaping; Structured light; Digital micro-mirror device; Diffractive optics; 3-D printing; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-11: Sustainable cities and communities